ANALISIS STRATEGI FUNGSIONAL TENTANG PENGARUH KOMITMEN DAN PARTISIPASI ANGGOTA TERHADAP KINERJA KOPERASI PEMERINTAH (Studi Kasus Koperasi Pegawai Kementerian Sosial RI) - Redjeki, Annie Martina; Purwoko, Bambang; W Sumarlin, Antonius (SEKOLAH PASCASARJANA PRESS, 2017)
onesia’s Cooperative is a basically a legal organization that manages the funds of its members to be put into a good use that caters the needs of the members. This type of organization is a common practice in Indonesia and can be formed byeither mandatory or voluntary membership. This paper investigates the strategic management issues of cooperative that consists of mandatory members because the common practice of this organization only relies on earnings from yields of bank savings / investments and lendings of its members. Questions often raised from this basic activities are whether the cooperative can elevate its portfolios more into non-financial businesses that bear higher yield earnings. In an attempt to answer the preceding, a cooperative set up by the government employees of Ministry of Social Affair is depicted for the object of study. There were 241 workers were stratifiedly sampled in accordance to their civil servant ranks. The distributed questionaires covered the issues of how member’s commitment and member’s participation affect the cooperative’s performances. The indicative results suggest that the commitment of cooperative members can only be increased by members’ participation in order to affect the performance of an organization.